2014
DOI: 10.1007/s11010-014-2164-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 520d-3p inhibits gastric cancer cell proliferation, migration, and invasion by downregulating EphA2 expression

Abstract: Aberrant expression of microRNAs (miRNAs) has been shown to play important roles in cancer progression as a result of changes in expression of their target genes. In this study, we investigated the roles of miR-520d-3p on gastric cancer (GC) cell proliferation, migration, and invasion, and confirmed that this miRNA regulates EphA2 expression. The mRNA expression levels of miR-520d-3p and EphA2 in GC tissues and cell lines were evaluated. The clinical and prognostic significance of miR-520d-3p was assessed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…MiR-520 also has been reported in GC [34]. However, to our knowledge, the study of the relationship between miR-520b/e and EGFR pathway in GC has not been reported.…”
Section: Effects Of Egfr On Proliferation and Migration In Gc Cellsmentioning
confidence: 85%
“…MiR-520 also has been reported in GC [34]. However, to our knowledge, the study of the relationship between miR-520b/e and EGFR pathway in GC has not been reported.…”
Section: Effects Of Egfr On Proliferation and Migration In Gc Cellsmentioning
confidence: 85%
“…Bach1, a negative regulator of Nrf2/EpRE activity, has been shown to be target of miR-196b [383], miR-155 [384], let-7b miRNA, let-7c miRNA, miR98 [385], and miR-122 [386]. Another negative regulator of Nrf2, c-Myc, was also regulated by miRNA, including miR-520d-3p [387], miRNA-135b [388], miR-34b/c [389], miR-744 [390], miR-184 [391], microRNA-135a [392], miR-145 [393] [394], miR-126 [395], miR-449c [396], miR-196b [397], miR-34a [398], miR-33b [399], miR-98 [400], miR-let-7 [400] [401] and miR-185-3p [402]. The Nrf2 partner, c-Jun is also targeted by miRNA miR-125b [403] and miR-155 [404].…”
Section: Introductionmentioning
confidence: 99%
“…inhibited cell proliferation and blocked p38MAPK and ERK1/2 pathways, whereas inhibiting miR-520e led to completely opposite results, and si-EphA2 reversed the effect of miR-520e inhibitor. Coincidentally, miR-520d-3p, another member of miR-520 family, could target EphA2 to suppress the proliferation, invasion and migration od gastric cancer cells, as indicated by Li et al, 44 and downregulation of EphA2 has been previously shown to inhibit Ras/MAPK pathway to inhibit tumour growth. 45 The above-mentioned findings demonstrated that miR-520e may block the downstream MAPK signalling pathway by targeting EphA2, consequently interrupting the HBV replication and cell proliferation of HBx-mediated HCC.…”
Section: Discussionmentioning
confidence: 93%